Investigation of American and Turkish mothers of preschooler’s perspectives about social-emotional development - UYANIK, GÜLDEN (My University, 2022)
The effect of mothers on the development of the children in the preschool period is quite clear. From birth, babies try to adapt to the new environment by forming a secure attachment relationship with their mother. Social-emotional development forms the basis of a child’s life-long ability to interact with others and to have a social life. There is very little research in the literature investigating the perspectives of mothers from different cultures on the social-emotional development of children, especially in the preschool period. From this point of view, the aim of the study, which was conducted using the qualitative research method consisting of semi-structured interview questions, is to compare the perspectives on the social-emotional development of preschool children between American (n = 34) and Turkish (n = 35) mothers. Content analysis of open-ended responses revealed numerous similarities, including how the mothers defined socialemotional development in terms of understanding and expressing feelings; emotional regulation; social communication and selfexpression; and adaptation to and interaction within social environments. Mothers in both cultures were also similar in the socialemotional skills desired for their children, including emotional expression, emotional regulation, and social values and skills related to self-identity. In terms of supporting this development, mothers provided emotional coaching, did activities with them, and arranged time with peers and other social experiences. In both cultures, mothers described three categories of worrisome behaviors including temper tantrums, determining if behavior is age-appropriate, and shyness. A noteworthy difference between Turkish and U.S. mothers was that the Americans’ believed preschool was important to children’s socialemotional development.

Annelerin okul öncesi dönem çocuklarının gelişimi üzerindeki etkisi oldukça açıktır. Bebekler doğdukları andan itibaren anneleriyle güvenli bir bağlanma ilişkisi kurarak yeni ortamlara uyum sağlamaya çalışırlar. Sosyal-duygusal gelişim, çocuğun yaşamı boyunca başkalarıyla etkileşim kurma ve sosyal bir yaşam sürme becerisinin temelini oluşturur. Alan yazında farklı kültürlerden annelerin özellikle okul öncesi dönemdeki çocukların sosyal-duygusal gelişimlerine yönelik bakış açılarını araştıran çok az araştırma bulunmaktadır. Bu noktadan hareketle yarı yapılandırılmış görüşme sorularından oluşan nitel araştırma yöntemi kullanılarak yapılan araştırmanın amacı Amerikan (n = 34) ve Türk (n = 35) anneler arasında okul öncesi dönem çocuklarının sosyal-duygusal gelişimine ilişkin bakış açılarını karşılaştırmaktır. Araştırma kapsamında kullanılan görüşme formundan elde edilen bulgular içerik analizi ile çözümlenmiş olup elde edilen temalar: annelerin duyguları anlama ve ifade etme açısından sosyal-duygusal gelişimi nasıl tanımladıkları; duygusal düzenleme; sosyal iletişim ve kendini ifade etme ve sosyal ortamlara uyum ve etkileşim şeklindedir. Elde edilen bulgular doğrultusunda her iki kültürdeki anneler, duygusal ifade, duygu düzenleme ve öz kimlikle ilgili sosyal değerler ve beceriler de dahil olmak üzere çocukları için arzu edilen sosyal-duygusal becerilerde benzer cevaplar verdikleri görülmüştür. Sosyal-duygusal gelişimin desteklenmesi açısından annelerin çocuklarına duygusal koçluk yaptığı, onlarla etkinlikler yaptığı, akranlarıyla zaman geçirmesi ve diğer sosyal deneyimleri sağlamışlardır. Her iki kültürde de anneler çocukları için öfke nöbetleri, davranışın yaşa uygun olup olmadığını belirleme ve utangaçlık dahil olmak üzere üç endişe verici davranış kategorisi tanımlamıştır. Türk ve Amerikan anneler arasındaki dikkate değer farkın ise Amerikan annelerin okul öncesi eğitimin çocukların sosyal-duygusal gelişimi için önemli olduğuna inandıklarını ifade etmiş olmalarıdır.
Okul öncesi dönemde çocuğu olan Türk ve Amerikalı annelerinin sosyal-duygusal gelişime yönelik bakış açılarının incelenmesi
Keywords: Sosyal-Duygusal Gelişim; Türk ve Amerikalı Annelerin Bakış Açıları; Okul Öncesi Dönem Çocuklar; al-Emotional Development; Turkish and American Mother’s Perspectives; Early Childhood Education